Evaluation of Antioxidant and Antimicrobial Capacity of Pomegranate Peel Extract (Punica Granatuml.) Under Different Drying Temperatures - L. Benossi Marchi; A.R. Monteiro; J. Mikcha; A. Santos; M. Chinelatto; D. Marques; A.S. Dacome; S.C. Costa (Chemical Engineering Transactions, 2015)
Pomegranate peels (Punica granatum L.) are considered non-edible parts or byproducts obtained during juice processing and characterized by the significant presence of polyphenols such as ellagitannins, ellagic acid, gallic acid and flavonoids, associated with biological properties such as antioxidant and antimicrobial agents. The objective of this study was to establish the antioxidant and antimicrobial capacity of aqueous and ethanolic extract of pomegranate peels, freeze-dried and oven dried to 60°C, through DPPH and ABTS radicals capture methods and Minimum Inhibitory Concentration with Escherichia coli ATCC 25922, Salmonella typhimurium ATCC 14028 and Staphylococcus aureus ATCC 25923, using 5000-625 µg/ml concentrations. The values indicated were the following: antioxidant activity of aqueous extract of freeze-dried pomegranate peels 595.71 ± 0.2 µmolTrolox / g (DPPH) and 1056.34 ± 0.4 µmolTrolox / g (ABTS);the ethanolic extract showed 586.96 ± 0.1 µmolTrolox / g (DPPH) and 1035.98 ± 0.2 µmolTrolox / g (ABTS), while the aqueous extract of dried peels at 60 °C presented 351,36±0,2 µmolTrolox/g (DPPH) and 871.73 ± 0.2 µmolTrolox / g (ABTS), and ethanolic extract with 359.21 ± 0.1 µmolTrolox / g (DPPH) and 885.04 ± 0.1 µmolTrolox / g (ABTS). Similar studies have indicated that pomegranate extracts are effective in inhibiting the growth of Escherichia coli and Staphylococcus aureus. In this study, the aqueous and ethanolic extracts revealed no inhibitory and bactericidal activity for E. coli and S. tyhimurium; in addition, despite the higher antioxidant activity present in the extracts of lyophilized peels, no better antimicrobial results were pointed. All extracts indicated bactericidal activity for S. aureus at a minimum concentration of 650 µg / ml of extract.